EBOLA: This catastrophe must never be allowed to happen again - Interview: David Nabarro, UN Special Envoy of the UN Secretary-General on Ebola - David Nabarro (Africa Renewal, 2014)
Following the Ebola virus outbreak, the United Nations set up its first-ever public health mission — the UN Mission for Ebola Emergency Response (UNMEER) — to deal with the pandemic. In this interview with Newton Kanhema for Africa Renewal, David Nabarro, the UN Secretary-General’s Special Envoy on Ebola, discusses the UN’s efforts to bring the virus under control.